(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2026)
Background: Diarrhea is a leading cause of childhood death in the world, account ing for 5-10 million deaths per year. Worldwide, rotavirus is estimated to cause more than 111 million cases of diarrhea annually in children younger than 5 year of age. It is considered as a major cause of childhood morbidity and mortality particu larly in developing countries like Bangladesh. Considering the high morbidity and significant mortality, this study was designed to determine the incidence of rotavirus and adenovirus associated diarrhea among under 2 years. Materials and methods: This cross-sectional study was conducted in the Department of Pediatric Gastroenterology, Chattogram Maa-O-Shishu Hospital Medical College from 1st September 2022 to 28th February 2023. Total of 150 patients were enrolled in this study who were admit with acute watery diarrhoea. Stool samples were obtained and assayed for rotavirus antigen by Immunochromatography Test (ICT) – ICT Quick Rotavirus kits (Arco Biotech, Germany) were used to detect rotavirus antigen in stool samples. Results: Viral antigens were detected in 116 (77.33%) out of 150 samples analysed during the study period. Of the antigen-positive samples,70(60.3%) belonged to boys and 46 (39.65%) belonged to girls. Of the total antigen-positive samples the Rotavirus antigen was identified in 101 (87.06%) specimens, the Adenovirus antigen was identified in 11 (9.48%) and Rota adeno was identified in 4 (3.44%) specimens. The high prevalence of rotavirus and adenovirus between the ages of 7 and 12 was found 47 (40.51%) and 6 (5.17%) respectively which is to be statistically significant (p < 0.05). High incidence rate of rotavirus infections in winter months was determined. This was found to be statistically significant (p < 0.05). Conclusion: This study showed a high prevalence of Rotavirus (67.33%) infection in patients under 2 years of age. Peak age incidence under 12 months and in January . Using the rotavirus vaccine in this population can reduce diarrhoea prevalence and eliminate unnecessary antibiotic use. Chatt Maa Shi Hosp Med Coll J; Vol.24 (2); July 2025; Page 97-101